APPLICATION OF RESTITUTION CRIME IN CASES OF MOLESTATION OF MINORS - Adnandito; Artadi, Ibnu; Ismayana (Hukum Responsif, 2024)
The provision of restitution rights as a form of compensation to children victims of criminal acts of molestation is becoming an interesting issue related to child protection because sexual violence is a type of violence with a high number every year. In this study, the author made 2 (two) problem formulations, namely: how to apply the criminal restitution in the crime of child molestation and what are the obstacles to the implementation of the provision of restitution. This study took a verdict in 2021 regarding cases of sexual abuse that positioned children as victims. The legal research method used is normative juridical which is qualitative to obtain descriptive results. The following are the results of the research that the author has found: The provision of restitution to children victims of criminal acts of abuse is the right of children of victims of criminal acts based on Article 7A of Law Number 13 of 2006, Article 71D of Law Number 35 of 2014 and Article 3 of Government Regulation Number 43 of 2017. An application for restitution can be submitted at the time before the judgment or after the judgment has obtained permanent legal force. So that the provision of restitution to the victim's child is not fundamental. Furthermore, the author found that there was a provision of restitution in the verdict so that the defendant was burdened with the obligation to pay restitution in the amount of Rp.331,527,186.00 (three hundred and thirty-one million five hundred and twenty-seven thousand one hundred and eighty-six rupiah) to the victim's children who had applied for restitution as many as 12 restitution applications. The Panel of Judges upholds procedural principles and does not look at the aspect of child protection.